Pt‐ and Pd‐Complexes with Acyclic and Heterocyclic P‐Hydroxyaryl‐Substituted N‐Phosphanylmethyl Amino Acids RP(CH2NHR')2 and (RPCH2NR'CH2)2 – Evaluation of (P^O)M Chelate Formation. Issue 38 (25th August 2020) - Karasik, Andrey A.; Heinicke, Joachim W.; Balueva, Anna S.; Thede, Gabriele; Jones, Peter G.; Sinyashin, Oleg G.
Abstract : P ‐Hydroxyaryl‐ and N ‐C6 H4 COOH‐substituted phosphanyl‐bis(methylamines) and 1, 5‐diaza‐3, 7‐diphosphacyclooctanes react with M II (cod)Cl2 (M II = Pt, Pd) to give the corresponding monophosphane L2 MCl2 and bisphosphane LMCl2 complexes. Spontaneous mono‐(P ^ O)M‐chelate formation was observed only for L2 PtCl2 involving 2‐C6 H4 OH groups and, partially, on heating the 8‐membered LPtCl2 complex. Addition of excess Et3 N led to a full conversion to the (P ^ O)MCl(P ^ OH) complexes with COOH groups, whereas heating the LMCl2 complexes with excess Na2 CO3 in DMF (4 h 90 °C) led to the formation of sodium salts of mono‐ and, in trace (Pt) or small (Pd) amounts, of bis(P ^ O)M‐chelates. The structures were established by multinuclear NMR data and for an LPdCl2 and a (P ^ O)PtCl(P ^ OH) complex by crystal structure analysis, in the latter case with the influence of a close C–H··· Cl–Pt contact on the (P ^ OH)‐conformation. Abstract : The reaction of o ‐hydroxyaryl‐substituted acyclic mono‐ and heterocyclic bis‐ N ‐phosphanylmethyl‐aminobenzoic acids with M(cod)Cl2 (M = Pt, Pd) furnished L2 MCl2 and LMCl2 complexes. First examples of amino acid‐based (P ^ O)M chelates complexes.